Ecumenical dialogue - Maffeis, Angelo, 1960- (Collegeville, Minn. : Liturgical Press, 2005)
"Surveys the historical and theological foundations of the ecumenical movement; special attention is given to conciliar ecumenism and to the dialogues to which the Roman Catholic Church is partner"--Provided by publisher.
Includes bibliographical references (p. 105-109).
Keywords: World Council of Churches; Christian union -- Catholic Church; Ecumenical movement